2012
DOI: 10.1038/npp.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Nucleus Accumbens Deep Brain Stimulation in Treatment-Resistant Depression: Evidence for Sustained Efficacy

Abstract: Deep brain stimulation (DBS) to the nucleus accumbens (NAcc-DBS) was associated with antidepressant, anxiolytic, and procognitive effects in a small sample of patients suffering from treatment-resistant depression (TRD), followed over 1 year. Results of long-term follow-up of up to 4 years of NAcc-DBS are described in a group of 11 patients. Clinical effects, quality of life (QoL), cognition, and safety are reported. Eleven patients were stimulated with DBS bilateral to the NAcc. Main outcome measures were cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
0
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(241 citation statements)
references
References 37 publications
7
223
0
11
Order By: Relevance
“…Lozano et al (31) demonstrated that it had 55% efficacy, with a follow-up record of 20 patients who underwent the surgery 3-6 years prior. In another group of patients with depression, the anterior limb of the internal capsule was regarded as the target of DBS therapy (32). One month post-surgery, the depressive symptoms of patients remitted were evaluated using the Montgomery-Asberg Depression Rating Scale (MADRS) (33).…”
Section: The Selection Of Different Targets For Dbs In Treating Mentamentioning
confidence: 99%
“…Lozano et al (31) demonstrated that it had 55% efficacy, with a follow-up record of 20 patients who underwent the surgery 3-6 years prior. In another group of patients with depression, the anterior limb of the internal capsule was regarded as the target of DBS therapy (32). One month post-surgery, the depressive symptoms of patients remitted were evaluated using the Montgomery-Asberg Depression Rating Scale (MADRS) (33).…”
Section: The Selection Of Different Targets For Dbs In Treating Mentamentioning
confidence: 99%
“…3,17,57 In most other disease trials for DBS, surgery was offered to patients with severe symptoms in whom medical therapy had failed, and who did not have any other major contraindications to DBS. 47 Trial design would largely depend on the proposed DBS target, but the need for a traditional Phase I clinical trial may be obviated by the fact that a reasonable safety profile has been largely established by previous pilot trials/studies of both LH 90 and NAc 3,17 targets.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…This trial should help clarify outstanding questions of efficacy and patient selection. Other targets under investigation include the ventral striatum/ nucleus accumbens, 22,23 inferior thalamic peduncle, and habenula.…”
Section: Current Practicementioning
confidence: 99%